Watch What They Do, Not What They Say : Estimating Regulatory Costs from Revealed Preferences - Alvero, Adrien (IMF Working Papers; Working Paper ;, 2022)
We show that distortion in the size distribution of banks around regulatory thresholds can be used to identify costs of bank regulation. We build a structural model in which banks can strategically bunch their assets below regulatory thresholds to avoid regulations. The resulting distortion in the size distribution of banks reveals the magnitude of regulatory costs. Using U.S. bank data, we estimate the regulatory costs imposed by the Dodd-Frank Act. Although the estimated regulatory costs are substantial, they are significatnly lower than those in self-reported estimates by banks.